2021
DOI: 10.1002/fsn3.2551
|View full text |Cite
|
Sign up to set email alerts
|

The physicochemical, microbiological, and organoleptic properties and antioxidant activities of cream cheeses fortified with dried curry leaves (Murraya koenigii L.) powder

Abstract: The demand for value-added dairy products is ever-growing, where consumers are seeking various functional and bioactive properties.As an attempt, diversification of cream cheese with several herbs and spices has been practiced. Cream cheese is a soft and white-colored cheese with a subtle and sweet flavor. Often, it is used as a spread (e.g., for bread, bagels, and crackers) and a dip (e.g., for potato chips) and used as an ingredient in many food applications (Sainani et al., 2004). Cream cheese is mainly aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…This marker would explain bioburden quality as total microbial count over distance from the reference entry point of the distribution water section. Moreover, the graph demonstrated correlated points at minor and gross levels [26]. Normally, the biological quality of the feeding source influences that of the distribution network.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This marker would explain bioburden quality as total microbial count over distance from the reference entry point of the distribution water section. Moreover, the graph demonstrated correlated points at minor and gross levels [26]. Normally, the biological quality of the feeding source influences that of the distribution network.…”
Section: Resultsmentioning
confidence: 90%
“…There was a shred of strong evidence for clustering tendency that could be observed in the left side of the y-axis in the score plot in Figure 3. Moreover, outlier values could be expected also as some remote and isolated values were spotted toward the edges at the right position above and below the +x-axis [20,26,28]. Sporadic high values in the database records were detected, despite no Out-Of-Specification (OOS) results could be detected as all results were below the regulatory acceptance specification limit of 100 CFU/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, MBE prevents the development of microorganisms during storage, which demonstrates their preservation potential. Similarly, Weragama et al [3] observed that untreated cream cheese showed lower pH values compared to samples of cream cheeses fortified with dried curry leaves (Murraya koenigii L.) powder during storage. Azarashkan et al [49] reported that the pH value of the samples of ricotta cheese with nano-encapsulated broccoli sprout extract was higher than that of the control.…”
Section: Evolution Of the Cream Cheese Fortified With Microencapsulat...mentioning
confidence: 92%
“…2 of 20 the food industry [3,5,7,8,9]. Basil extract is characterized by high antioxidant and antimicrobial activity [9,10], contributing to reducing the population of pathogenic microorganisms and to the expansion of shelf life of perishable food products [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, o‐methylmurrayamine A, mukolidine and murrayakonine A were able to inhibit the release of IL‐6, TNF‐α in LPS‐induced inflammation [73] . The pharmacological activities of various extract on M. koenigii (L.) Spreng are discussed in Table 4 [39,45–46,58,62,69–70,74–149] and Figure 5 along with various patents on M. koenigii (L.) Spreng showed in Table 5 [150–157]…”
Section: Pharmacological Activitiesmentioning
confidence: 99%